KLONING DAN OVEREKSPRESI PROTEIN P24-GAG HIV (Cloning and Overexpression P24-Gag of HIV) - Efrida Efrida; Andani Eka Putra (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
HIV diagnosis is confirmed by viral culture, but this process takes a long time. Another method used to detect HIV-specific antigensor antibodies is by immunoassay. Generally, antigen-antibody based methods are used as a screening test. Based on the stability ofthe sequences found in the first (1) study year, the researchers designed this study for the production of p24 recombinant protein.These proteins will be developed as diagnostic markers based on sero-immunology technique. The aim of this study was to know theconstruction and over expression of protein p24gag from local isolates and analysis of the diagnostic potential of doing design specificprimers against p24gag protein, cloning and over expression of the gene, as well as to obtain a p24 protein that has been purified.This research results will be applied later to develop a method based on local isolates of HIV diagnosis. This research was a descriptivestudy, conducted over seven (7) months in the Biomedical Laboratory of the Faculty of Medicine, Andalas University and Departmentof Clinical Pathology, Dr. M. Djamil Hospital, Padang. This study was carried out by using samples of local isolates originating fromthe first year of research. Stages of the research were: 1) the design of primers for cloning, amplification and sequencing, 2) cloninginto pDEST and pENT, 3) transformation of the target gene, 4) detection of fragment insertions, 5) protein expression and proteinanalysis by SDS-PAGE, immunoblotting and 6) purification. The conclusions of this study were: the design of specific primers againstp24gag protein used fragments attb1, attb2, Shine Delgano and Kozac effective for protein expression. The results showed that thepresence of protein 24kDa expression was identical to HIV p24gag protein. Further research needs to be conducted to identify potentialimmunological target protein.